1982
DOI: 10.1115/1.3227268
|View full text |Cite
|
Sign up to set email alerts
|

A Theory for Fine Particle Deposition in Two-Dimensional Boundary Layer Flows and Application to Gas Turbines

Abstract: A theory is presented to predict deposition rates of fine particles in two-dimensional compressible boundary layer flows. The mathematical model developed accounts for diffusion due to both molecular and turbulent fluctuations in the boundary layer flow. Particle inertia is taken into account in establishing the condition on particle flux near the surface. Gravitational settling and thermophoresis are not considered. The model assumes that the fraction of particles sticking upon arrival at the surface is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
5

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
11
0
5
Order By: Relevance
“…For 0.01<d < 1.0 um it is the eddy one and thermophoresis,while for p>1.0 µm, it is the inertial forces. The deposition of particles and droplets on turbine cascades has been studied by Moore and Crane [5],Grane [6], Menguturk and Sverdiap [7], Yau and Young [8], all based on calculation codes that incorporated a proper deposition velocity model. Detailed experimental data for the deposition rate are almost non-existent, except for the isothermal flow one by Parker and Lee [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For 0.01<d < 1.0 um it is the eddy one and thermophoresis,while for p>1.0 µm, it is the inertial forces. The deposition of particles and droplets on turbine cascades has been studied by Moore and Crane [5],Grane [6], Menguturk and Sverdiap [7], Yau and Young [8], all based on calculation codes that incorporated a proper deposition velocity model. Detailed experimental data for the deposition rate are almost non-existent, except for the isothermal flow one by Parker and Lee [9].…”
mentioning
confidence: 99%
“…THE The eddy diffusion model to be employed was that of Yau and Young [8]. This is a somewhat simpler numerically model to the one of Menguturk and SverdZap [7],since the last assumes a streamwise mass diffusion. The basic philosophy,however,of the two models is the same,that is the "stopping distance" model of Friedlander and Jonston [20].…”
mentioning
confidence: 99%
“…1 presents the particle distributions considered by the various workers in cascade deposition and erosion studies. As it can be seen, there exist basically two distributions which correspond in general to ash (1,4,5) and air dust and sand particles (9,10,11,12). The present study deals with the first distribution, typical of PFBC plants.…”
Section: -Gt-345mentioning
confidence: 94%
“…Solid particles are transfered to the blade surfaces by inertia, eddy diffusion, Brownian motion and thermophoresis. Previous work (1,4,5,6,7,8) has shown that smaller particles (d < 0.01 pm) are transported to the blades mainly by Brownian diffusion, larger particles (0.01 -1 pm) by eddy diffusion and thermophoresis, while supermicron particles are guided by inertial forces, resulting in blade erosion. Smaller particles which stick on the blade surface through adherence forces form a sticky layer on which larger particles agglomerate.…”
Section: -Gt-345mentioning
confidence: 97%
“…Models (10) have also been developed to predict particle delivery to turbine airfoil surfaces due to diffusion. Figure 2 illustrates model results for particle delivery rates due to the combined effects of turbulent eddy and Brownian diffusion.…”
Section: Mechanisms Of Deliverymentioning
confidence: 99%